ANALISA DAN DESIGN MENGGUNAKAN UNIFIELD MODELLING LANGUAGE (UML) APLIKASI PENERIMAAN SISWA BARU ONLINE (SIAP-PSB ONLINE) PADA SMA AL-HUDA ISLAMIC EDUCATION CENTRE METROPOLITAN (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2024)
AbstractRapid development of science and technology, especially in the field of the internet wasinstrumental in various aspects of social life. Including in terms of information needs. As for thepurpose of this research is to help make it easier in terms of admission to publicschools or private way based website using PHP and MySQL as a database. Meanwhile, themethods used in the development of the system itself uses the model of the waterfall, i.e. bydoing observation directly towards the object of research on systems that are running at themoment. Design your own system using object-oriented methods and in the design process isdescribed using UML (Unfield Modelling Language). The resulting system was later expectedto address the problems that exist and can help make it easier for prospective students who wish toregister or the school in carrying out the activities of the acceptance of new students at the HIGHSCHOOL of AL-HUDA ISLAMIC EDUCATION CENTRE METROPOLITAN (IECM).